E-GOVERNANCE SERVICES FOR SUSTAINABLE LIVELIHOODS: MDGS BASED ASSESSMENT - Harekrishna, Misra (Social Sciences Research Society, 2018)
Millennium Development Goals (MDG) initiative with set of eight goals contribute to sustainable livelihoods. Persistence of digital divides in the form of affordability, access to technology, usage and usability of the services rendered and deficits in good E-governance have impeded the achievement of goals. EGovernance services in India aim to address these issues and are in process of scaling to reach rural households. Converged e-governance services in India strive to capture local knowledge for wider dissemination, and enables rural households to augment their livelihoods. The paper assesses availability of e-governance services in supporting sustainable livelihoods of rural households in Mahabubnagar district in the state of Andhra Pradesh.